2005
DOI: 10.1017/s0790966700008715
|View full text |Cite
|
Sign up to set email alerts
|

Stimulant medication in ADHD: what do children and their parents say?

Abstract: Objectives: The prescription of stimulant medication to children with attention deficit hyperactivity disorder remains topical. Few reports target children's views about taking long-term medication. The aim was to assess child and parent views of stimulant medication. To compare attitudes to medication between two groups of children, those with attention deficit hyperactivity disorder taking stimulant medication and those with epilepsy taking anti-epileptic medication.Method: Forty children (n = 40) with atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Another study investigating children's attributions about having ADHD, found that these children reported that their behavior is out of their control and global across situations (Kaidar, 2004). Similarly, children with ADHD have been able to report on the benefits of taking stimulant medication, with one study reporting that two-thirds of children with ADHD reported positives in taking stimulant medication (McElearney, Fitzpatrick, Farrell, King, & Lynch, 2005). In addition, children with ADHD have been reported to maintain their sense of self while taking medication (Singh, 2007).…”
mentioning
confidence: 99%
“…Another study investigating children's attributions about having ADHD, found that these children reported that their behavior is out of their control and global across situations (Kaidar, 2004). Similarly, children with ADHD have been able to report on the benefits of taking stimulant medication, with one study reporting that two-thirds of children with ADHD reported positives in taking stimulant medication (McElearney, Fitzpatrick, Farrell, King, & Lynch, 2005). In addition, children with ADHD have been reported to maintain their sense of self while taking medication (Singh, 2007).…”
mentioning
confidence: 99%
“…Some researchers seek to draw a connection between the severity of the behavioural symptoms of the child diagnosed with ADHD and possible parental weaknesses, including the mother's sense of incompetence (McLaughlin & Harrison, 2006), mother-son relations (Wallace, 2005), parental anxiety and family functioning (Kashdan et al, 2004), and parents' inability to use diagnostic grids of objective measures (Curko, Marks, Berwid, Santra, & Halperin, 2004). Investigators also examine parental influence on the attitudes of children regarding medication as a function of the parents' expectations (McElearney, Fitzpatrick, Farrell, King, & Lynch, 2005;Traywick, Lamson, Diamond, & Carawan, 2006). Other researchers, though, seek to understand the experiences of parents by studying the effect of receiving a diagnosis (Gerdes, 2005;Saltmarsh, McDougall, & Downey, 2005).…”
Section: Processes Of Influence Exerted By Scientific Actors On Paren...mentioning
confidence: 99%
“…Meaux, Hester, Smith, and Shoptaw (2006) found social stigma and feeling different from peers were reasons why children stopped taking medications for ADHD. In addition, McElearney, Fitzpatrick, Farrell, King, & Lynch (2005) found only 32% of children who were taking stimulant medication for ADHD were willing to tell their peers that they were on medication.…”
Section: Introductionmentioning
confidence: 99%